2018
DOI: 10.1523/jneurosci.0984-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cholinergic Midbrain Neurons in Startle and Prepulse Inhibition

Abstract: One of the two major cholinergic centers of the mammalian brain is located in the midbrain, i.e., the pedunculopontine tegmentum (PPTg) and the adjacent laterodorsal tegmentum. These cholinergic neurons have been shown to be important for e.g., arousal, reward associations, and sleep. They also have been suggested to mediate sensorimotor gating, measured as prepulse inhibition of startle (PPI). PPI disruptions are a hallmark of schizophrenia and are observed in various other psychiatric disorders, where they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 73 publications
3
36
2
2
Order By: Relevance
“…The anatomical connection between the SC and the pedunculopontine tegmental nucleus (PPTg) activates a cholinergic projection to the PnC that mediates the PPI. In contrast to the longstanding hypothetical view that PPI is mediated by cholinergic PPTg neurons, recent studies applying optogenetics in rats [ 94 ] or using selective cholinergic lesion in PPTg [ 95 ] have demonstrated that the non-cholinergic PPTg neurons mediate PPI, whereas cholinergic neurons of PPTg enhance startle and lead to prepulse facilitation [ 94 ]. This controversy should be explored further to clarify the presumed role of PPTg cholinergic neurons in the sensory gating mechanisms of the ASR.…”
Section: Neuronal Pathways Of the Acoustic Startle Reflex And Its mentioning
confidence: 99%
“…The anatomical connection between the SC and the pedunculopontine tegmental nucleus (PPTg) activates a cholinergic projection to the PnC that mediates the PPI. In contrast to the longstanding hypothetical view that PPI is mediated by cholinergic PPTg neurons, recent studies applying optogenetics in rats [ 94 ] or using selective cholinergic lesion in PPTg [ 95 ] have demonstrated that the non-cholinergic PPTg neurons mediate PPI, whereas cholinergic neurons of PPTg enhance startle and lead to prepulse facilitation [ 94 ]. This controversy should be explored further to clarify the presumed role of PPTg cholinergic neurons in the sensory gating mechanisms of the ASR.…”
Section: Neuronal Pathways Of the Acoustic Startle Reflex And Its mentioning
confidence: 99%
“…The PPT extends rostro-ventrally from this location almost as far as the substantia nigra in the rostral and ventral midbrain. Nearly half of the neurons in the PPT region respond to sound, and the cholinergic neurons have been implicated in acoustic startle and tone-specific plasticity (e.g., Reese et al, 1995a , b , c ; Xiong et al, 2009 ; Suga, 2012 ; Azzopardi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this evidence, DA availability in the NAc seems to be critical in determining the level of PPI observed; i.e., a higher DA level will induce a PPI deficit, while a lower DA level will increase PPI (Arenas et al, 2017). The role of DA in determining PPI levels has been bolstered since activation of midbrain cholinergic neurons has been shown not to mediate PPI levels (Azzopardi et al, 2018). One of the main brain nuclei that modulate PPI is the pedunculopontine tegmentum (PPTg; Arenas et al, 2017), which is one of the major cholinergic centers of the brain (Gut and Winn, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main brain nuclei that modulate PPI is the pedunculopontine tegmentum (PPTg; Arenas et al, 2017), which is one of the major cholinergic centers of the brain (Gut and Winn, 2016). However, it has recently been demonstrated that cholinergic PPTg neurons do not mediate PPI, in contrast to a longstanding hypothesis maintaining that they do (Azzopardi et al, 2018). Furthermore, the lack of motor and rewarding effects of cocaine observed in the mice with a low PPI level may reflect an altered DA system.…”
Section: Discussionmentioning
confidence: 99%